2017
DOI: 10.17309/tmfv.2017.2.1193
|View full text |Cite
|
Sign up to set email alerts
|

Informative Indicators of 14-15 Years’ Age Boys’ Motor Fitness

Abstract: The purpose of the research is to determine informative indicators for in-group and intra-group control of 14 and 15 years’ age boys’ motor fitness.  Material & methods: in the research 112 schoolchildren participated: 14 years’ age (n=44), 15 year’ age (n=68). The materials of the research were processed in program of statistical analysis IBM SPSS 20. Factorial analysis as well as discriminant were fulfilled.  Results of the research: it was found that for control of motor fitness the most inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
8
0
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 58 publications
2
8
0
1
Order By: Relevance
“…The above-mentioned results show that discriminant analysis allows to identify the state of motor abilities development in boys aged 12-14 by the results of testing and supplement data on the use of discriminant function in classifying schoolchildren by motor activity (Gert-Jan de Bruijn, & Benjamin Gardner, 2011; Lulzim, 2013). As in the papers by Broadhead and Church (1982), Ivashchenko, Kapkan, Khudolii, and Yermakova (2017), Ivashchenko, Khudolii, Iermakov, Veremeenko, and Lopatiev (2018), we observed a high discriminative and predictive ability of these functions in evaluating motor preparedness of boys aged 12-14. The study confirmed that multidimensional methods of mathematical statistics such as factor and discriminant analyses (Ivashchenko, 2014;Lopatiev, Ivashchenko, Khudolii, Pjanylo, Chernenko, & Yermakova, 2017;Ivashchenko, Khudolii, Iermakov, Chernenko, & Honcharenko, 2018) are effective for studying the structure of motor preparedness of boys aged 12-14.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The above-mentioned results show that discriminant analysis allows to identify the state of motor abilities development in boys aged 12-14 by the results of testing and supplement data on the use of discriminant function in classifying schoolchildren by motor activity (Gert-Jan de Bruijn, & Benjamin Gardner, 2011; Lulzim, 2013). As in the papers by Broadhead and Church (1982), Ivashchenko, Kapkan, Khudolii, and Yermakova (2017), Ivashchenko, Khudolii, Iermakov, Veremeenko, and Lopatiev (2018), we observed a high discriminative and predictive ability of these functions in evaluating motor preparedness of boys aged 12-14. The study confirmed that multidimensional methods of mathematical statistics such as factor and discriminant analyses (Ivashchenko, 2014;Lopatiev, Ivashchenko, Khudolii, Pjanylo, Chernenko, & Yermakova, 2017;Ivashchenko, Khudolii, Iermakov, Chernenko, & Honcharenko, 2018) are effective for studying the structure of motor preparedness of boys aged 12-14.…”
Section: Discussionsupporting
confidence: 81%
“…The study confirmed that multidimensional methods of mathematical statistics such as factor and discriminant analyses (Ivashchenko, 2014;Lopatiev, Ivashchenko, Khudolii, Pjanylo, Chernenko, & Yermakova, 2017;Ivashchenko, Khudolii, Iermakov, Chernenko, & Honcharenko, 2018) are effective for studying the structure of motor preparedness of boys aged 12-14. The study added that he use of discriminant function in the analysis of standardized and structure coefficients allows to determine the structure of strength abilities development and their interrelation with endurance in boys aged 12-14 (Ivashchenko, 2017;Ivashchenko, Kapkan, Khudolii, Yermakova, 2017;Ivashchenko, Khudolii, Iermakov, & Harkusha, 2017).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The factor with the greatest correlation is the following: It is confirmed that multidimensional methods of mathematical statistics are effective for the study of the strength training structure of girls aged 12-14 years: factor and discriminant analysis [7,20]. It is added that the use of factor analysis allows to determine the structure of the development of power abilities and their interrelation with endurance in girls aged 12-14 years [21,22].…”
Section: Pedagogics Psychologymentioning
confidence: 99%
“…Multidimensional methods of mathematical statistics such as factor and discriminant analysis [7,20] are effective for studying the structure of motor readiness of schoolchildren. Using factor analysis allowed to establish the structure of motor readiness of schoolchildren [21,22]. However, in available literature there is not enough data on the peculiarities of the structure of power abilities development among middle class students.…”
Section: Introductionmentioning
confidence: 99%